Conflits autour d’une temporalité marchande dans les boutiques de réseaux - Rachid Bouchareb (Temporalités)
This paper focuses on standards of availability induced by the commercial temporality and employees’ resistances to a maximum flexibility. It is based on a fieldwork study in chain store shops located in France and Belgium. We study the principles of commercial organization through managerial practices of adaptation to commercial flow and the subordination of workers to employment times. In order to become more profitable, chain stores try to adjust the presence of their personnel to the variations of customers’ flows. Managers are in charge of this maximization of the profitability, therefore they expect their personnel to be flexible. It puts strong pressure on them, but it also gives birth to resistances against this constraint. Such resistance takes place in reaction to arbitrary changes of working days or hours; it can also lead them to refuse to work extra hours or to switch temporarily to full-time work.